Actual characteristics of nutrition of the population in Odessa region - Kovalchuk, L. Y.; Melnyk, K. S.; Mykhaylenko, V. L.; Badiuk, N. S. (Journal of Education, Health and Sport, 2017)
Kovalchuk L. Y., Melnyk K. S., Mykhaylenko V. L., Badiuk N. S. Actual characteristics of nutrition of the population in Odessa region. Journal of Education, Health and Sport. 2016;6(11):731-740. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.228325 http://ojs.ukw.edu.pl/index.php/johs/article/view/4132 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 30.11.2016. Actual characteristics of nutrition of the population in Odessa region L. Y. Kovalchuk, K. S. Melnyk, V. L. Mykhaylenko, *N. S. Badiuk Odessa National Medical University, Odessa, Ukraine *Ukrainian Research Institute of Transport Medicine of the Ministry of Health of Ukraine Summary Study of hygiene and environmental problems in the Odessa region should be aimed at the preservation of public health by minimizing the negative impact of environmental factors. Nutrition is one of the most important factors. Actual direction of modern medical science is the study of dietary intake and nutritional status of specific population groups to establish correlation between nutrition and health.Odessaregion differs significantly from other regions ofUkraineon the national population structure. The features of the modern structure of nutrition of the local population is the lack of animal protein, polyunsaturated fatty acids (in the face of excess animal fat intake), many vitamins, micro- and macronutrients, dietary fibers. Recently, in the region there is a problem of nutritional rationalizing for people coming into the territory of theOdessaregion from different geographical areas for long term. Scientific substantiation of preventive measures to optimize the nutrition of the population ofOdessaregion and establish the correlation with indicators of health status, disability, and the main components of lifestyle are important for the prevention of nutrition-caused diseases and improve the health of the population of theSouth Ukraine. Keywords: public health, structure of nutrition, dietary intake ,regional differences.